2001
DOI: 10.1128/aem.67.8.3440-3444.2001
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-Scale Evidence for Lightning-Mediated Gene Transfer in Soil

Abstract: Electrical fields and current can permeabilize bacterial membranes, allowing for the penetration of naked DNA. Given that the environment is subjected to regular thunderstorms and lightning discharges that induce enormous electrical perturbations, the possibility of natural electrotransformation of bacteria was investigated. We demonstrated with soil microcosm experiments that the transformation of added bacteria could be increased locally via lightning-mediated current injection. The incorporation of three ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…In soil, salt concentrations are described as compatible with the induction of a competent phase (18). In addition, Demanèche et al (8) showed that the electrical parameters occurring during electroporation (in vitro) were similar to those in soil microcosms subjected to lightning-mediated current injection (in situ). Moreover, these authors provided evidence for lightningmediated gene transfer (electrotransformation) of an E. coli strain in sterile soil.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In soil, salt concentrations are described as compatible with the induction of a competent phase (18). In addition, Demanèche et al (8) showed that the electrical parameters occurring during electroporation (in vitro) were similar to those in soil microcosms subjected to lightning-mediated current injection (in situ). Moreover, these authors provided evidence for lightningmediated gene transfer (electrotransformation) of an E. coli strain in sterile soil.…”
mentioning
confidence: 99%
“…E. coli strain DH10B was used as the positive control (8), and P. fluorescens C7R12 was used as the Pseudomonas reference strain. The soil experimental system used (soil from Côte Saint-André, France) was the same as that previously described (8). The soil was dried before ␥-sterilization (25-kGy; IONISOS, Dagneux, France).…”
mentioning
confidence: 99%
“…antibiotic resistance and virulence genes) and then fuse with another bacterium (Dorward et al, 1989;Kadurugamuwa and Beveridge, 1997;Yaron et al, 2000). -Virus-like particles (gene transfer agent) formed from proteins encoded by some bacterial genomes, which can trap random fragments of the genome (about 4400-13 600 base pairs) and transmit them to a second bacterium (Dykhuizen and Baranton, 2001;Lang and Beatty, 2001;Marrs, 1974 (Bos, 1999), by lightning in a manner analogous to genetic modification by electroporation (Demanèche et al, 2001) or desiccation (Gladyshev et al, 2008).…”
Section: Translocation Of Genetic Materialsmentioning
confidence: 99%
“…The fact that there is an intronic open reading frame with endonuclease activity in at least one strain (6,7,24) suggests that this intron is capable of mobility. On the other hand, recent evidence (12) suggests that lightning-mediated gene transfer could take place in soil and might be a mechanism involved in bacterial evolution. The introns from this family FIG.…”
Section: Fig 3 Pcr Amplification Of Trnamentioning
confidence: 99%